40.6k views
4 votes
Evaluate: f(x) = 2x^2 + 6x - 4; f(-5) *

User Elranu
by
5.4k points

2 Answers

2 votes

Answer:

f(-5)=126

Explanation:

what you would do first is plug -5 in for x which would give you the equation of f(-5)= 2(-5)^2 + 6(-5) -4

then you multiply the negative 5 and you will get

f(-5)= -10^2 + 30 -4

remove that square by multiplying -10 by -10 and you will get

f(-5)= 100 + 30 -4

combine like terms and you will get

f(-5)=126

i hope this helped you and that i explained it to you in a way that you understand

User Anish Anil
by
5.0k points
6 votes


f(x)=2x^2+6x-4\\

Find f(-5) by substituting x = -5 in the equation.


f(-5)=2(-5)^2+6(-5)-4\\f(-5)=2(25)-30-4\\f(-5)=50-34\\f(-5)=16

Therefore, the answer is f(-5) = 16

User Mohit Gupta
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.